A study on the estimation of serum lipid profile and homocysteine in coronary artery disease - UMA UNNIKRISHNAN; K M JAYADEVAN (International Journal of Pharma and Bio Sciences, 2017)
Coronary artery disease occurs due to inflammation and endothelial dysfunction of the blood vessels also known as atherosclerosis. The nonessential sulphur containing amino acid Homocysteine is considered to be a risk factor for myocardial infarction caused by damage to coronary arteries. The study was conducted on 60 individuals which included 30 cases of coronary artery disease diagnosed by angiography and 30 normal healthy individuals. Lipid profile and Homocysteine was estimated and compared among the two groups. There was a significant increase in Homocysteine in cases but no significant difference in lipid profile when compared to controls. Hence this study was done to indicate that Homocysteine can be considered as a risk factor for coronary artery diseases.